POLITICAL DEMOCRACY AND JUDICIAL VALUES: A PHILOSOPHICAL APPROACH TO JUSTICE AND DEMOCRACY THROUGH LEGAL PHILOSOPHY - Prasetyo, Dr. Dossy Iskandar (YURIS: Journal of Court and Justice, 2024)
This research analyzes the political democracy that is based on the fourth principle of Pancasila and the legal value from the perspective of legal philosophy. Legal philosophy research is directed at understanding the moral and legal imperatives contained in the concept of political democracy according to the fourth principle of Pancasila. This research uses a doctrinal legal method with a theoretical approach to find the conceptual basis of legal principles and examine the cumulative effect of various rules and procedures in a particular area of activity. There are two important points produced from this research, which are (1) the judicial values of political democracy in the fourth principle of Pancasila are closely related to Soekarno’s perception of Pancasila as the ideology of Indonesian people, which prioritizes harmonious life in diversity; (2) there are four main values in political democracy in the fourth principle of Pancasila, such as (a) democracy must be based on morals, (b) power must be used for the welfare of the people, (c) elections must be held with ethics and good manners, and (d) decisions must be reached through deliberation and consensus for the common good.